Implementasi Program MBG Untuk Meningkatkan Gizi Anak Sekolah Dasar di Kota Semarang 2025 - Nurulaini, Risma; Afifah, Dian Fitriani (CV. Green Publisher Indonesia, 2025)
This study analyses the implementation of the Free Nutritious Food Programme (MBG) in primary schools in Semarang City as an effort to prevent stunting and improve the nutrition of children from underprivileged families. With a stunting prevalence of around 30% based on the 2022 Indonesian Nutrition Status Survey, this programme aims to provide free nutritious meals in accordance with Minister of Education and Culture Regulation No. 30 of 2023, in line with the 2020-2024 National Medium-Term Development Plan (RPJMN). Pressman and Wildavsky's (1984) theory was used to understand the gradual implementation process, multi-sector coordination, and field adaptation. Qualitative methods were applied through semi-structured interviews with teachers, students, health workers, and food providers, followed by thematic analysis. The results show that the programme is running smoothly with increased student attendance and focus, despite logistical challenges, inter-agency coordination, and menu preferences. The conclusion emphasises the positive impact on nutrition and learning motivation, with recommendations for improved coordination, menu innovation, and community participation for programme sustainability.